The use of modality markers to perform hegemony politeness in using Balinese language: a case study on Awig-awig - Nengah Arnawa; I Wayan Gunartha; I Nyoman Sadwika (English, 2017)
This research was aimed at expressing motivation to use modality markers in text of traditional village regulation (awig-awig). The data was obtained from some major regulations in five regencies and city in Bali province. Sampling was done based on area considering dialectical and sociocultural diversity. Based on theory of pragmatics, it could be concluded that the use of Balinese language modality in text of traditional village regulation was not merely demanded by syntax and grammatical semantics. It can be proven with deletion technic. Upon the modality deletion, it did not change the prime meaning of text, but the sentences were still grammatical instead. The use of modality was motivated with pragmatic needs, i.e. performing hegemony politeness in accordance with the sense of modality as interpersonal rhetoric.